A simulação clínica no desenvolvimento de competências pedagógicas e profissionais em enfermagem - Ormonde Junior, Juarez Coimbra (2022)
Nursing professors and preceptors can adopt clinical simulation as a strategy to improve clinical competence, with positive effects on pedagogical and professional training. However, investigating how these actors perceive this phenomenon is complex and demands immersion in active processes of action and reflection. In this sense, this research starts from the intrinsic relationship between competences and simulation, to seek to reveal the understandings about their contributions in the context of training. Objective: To analyze the contributions of clinical simulation in the development and assessment of clinical competences by nursing professors and preceptors. Method: Simulation-based, descriptive, and exploratory research with a quantitative-qualitative approach. Data collection took place at the Health Simulation Center of the Júlio Müller University Hospital, linked to the Federal University of Mato Grosso. An event called “Clinical Simulation Workshop: Theory and Practice” was offered. The sample consisted of 52 (n=52) professors and preceptors from five higher education institutions in nursing in Cuiabá-MT and the metropolitan region. The simulation had as its theme “Nursing care for patients with pressure injuries”. Qualitative data were treated using Bardin's thematic analysis and for quantitative data, descriptive statistics were used. The results were considered significant with p<0.05 and a confidence level of 95%. Reliability and internal consistency were assessed using Cronbach's alpha. Results: There was a significant increase in the gain of cognitive knowledge, measured by the application of pre and post-test. Clinical simulation was effective as a teaching-learning method, being well evaluated in terms of design (average of 4.67), and satisfaction and self-confidence (average of 4.60). The evaluation of the debriefing was positive (average of 4.48) and allowed reflections on the performance and learning of the participants. About performance evaluation, it was observed that most evaluators had a consensus as to whether to perform certain actions. They agreed with 57.6% of the answers and disagreed with 42.4%. Overall, the scales showed good reliability and internal consistency. About qualitative analysis, three themes emerged, namely: 1) The constituent elements of clinical competence; 2) The development of clinical competences mediated by clinical simulation and 3) The evaluation of clinical competence performances. Participants understand clinical competence as a multidimensional, complex, and dynamic phenomenon, and that clinical simulation, as an active teaching-learning methodology, can contribute to its development, improvement, and evaluation. Final considerations: The structuring of reliable clinical scenarios that lead participants to learn in a critical and reflective way based on their experiences is viable and contributes to the development of clinical competences. They help to consolidate the knowledge required for practice, reducing gaps between know-how and bringing teachers and preceptors together. We suggest the inclusion of this methodology in the training context and in permanent education, as well as a curricular component in undergraduate and graduate nursing courses.